An Overview of Cardiorespiratory Health of Generation Z Vapers: A Qualitative Study - Ira Ayu Ananda; Beti Kristinawati (UIMA Press, 2024)
Abstract Background: The use of vape among generation Z is increasing.Vape users have the perception that vape is safer than conventional cigarettes. The effects caused by vape are very complex, one of which is cardiorespiratory. Objective: This study aims to explore the health conditions of the cardiorespiratory status of generation Z vapers. Methods: This study uses a qualitative method with a descriptive phenomenological approach. The sample was a number of generation Z aged 19-23 years old. Data was collected through in-depth interviews and analyzed using the Colaizzi technique. Results: The results of the study identified ten main themes, namely the social environment is a trigger factor for vape use in generation Z, vape use becomes a coping mechanism in generation Z, the frequency of vape use is influenced by the activities carried out by generation Z vapers, variations in taste and aroma affect the frequency of vape use, cardiorespiratory health problems experienced by generation Z after using vape, generation Z experiences health problems after using vape, generation Z vapers have different perceptions about vape use, vape addiction in generation Z vapers, there is a desire to stop using vape, and generation Z vapers minimize the effects of vape use by living a healthy lifestyle. Conclusion: Vape use has a negative impact on the cardiorespiratory health of generation Z. A multidimensional approach is needed to address the issues facing generation Z vapers.